2014
DOI: 10.1007/s10529-014-1733-9
|View full text |Cite
|
Sign up to set email alerts
|

GhDRIN1, a novel drought-induced gene of upland cotton (Gossypium hirsutum L.) confers abiotic and biotic stress tolerance in transgenic tobacco

Abstract: A novel stress tolerance cDNA fragment encoding GhDRIN1 protein was identified and its regulation was studied in cotton boll tissues and seedlings subjected to various biotic and abiotic stresses. Phylogenetic and conserved domain prediction indicated that GhDRIN1 was annotated with a hypothetical protein of unknown function. Subcellular localization showed that GhDRIN1 is localized in the chloroplasts. The promoter sequence was isolated and subjected to in silico study. Various cis-acting elements responsive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Upland cotton is widely cultivated around the world. Previous studies have shown that biotic and abiotic stresses adversely affect the normal growth and fiber quality of this crop ( Dhandapani et al, 2015 ). To gain further insights into the expression patterns of GhZHD genes, we used the available RNA-Seq data for fiber development, abiotic/biotic stress, tissue and organ development, and developmental biology.…”
Section: Resultsmentioning
confidence: 99%
“…Upland cotton is widely cultivated around the world. Previous studies have shown that biotic and abiotic stresses adversely affect the normal growth and fiber quality of this crop ( Dhandapani et al, 2015 ). To gain further insights into the expression patterns of GhZHD genes, we used the available RNA-Seq data for fiber development, abiotic/biotic stress, tissue and organ development, and developmental biology.…”
Section: Resultsmentioning
confidence: 99%